The Interpretation of Public Service Announcement: A Semiotic Analysis of Public Facilities and Television in Indonesia and Malaysia - Rozi , Fahrur; ., Tusyanah; April Farida, Lulu; Najmuddin Purwanto, Hadziq; Arviana Rizky, Nerisa (KnE Social Sciences, 2022)
This study analyzes the language used in public service announcements via public facilities and televisions in Indonesia and Malaysia. The method used is the qualitative research approach. Public facilities and television were analyzed as the objects of this study. The researchers used documentation and observation for collecting data and used Barthes’ theory to examine the public service announcements used. The result showed that public service announcements communicated in Indonesia and Malaysia have some similarities and some differences. They can be seen in languages, contents, colors, media, and designs used for and the places where the announcements were made. This article presents an analysis framework and rarely do any studies defy such attempts in a critical manner. Keywords: semiotics, analysis, public notices, publishing